Evaluation of Ca/P Ratios in Infant Milk Samples by CH4-Ar Mixed Plasma-DRC-MS - Guo, Wei; Jin, Lanlan; Hu, Shenghong (Asian Journal of Chemistry, 2014)
Methane mixed plasma dynamic reaction cell mass spectrometry was successfully used for accurate determination of Ca and P and Ca/P ratios in infant milk samples. The interfering 40Ar+ at m/z 40 was reduced in intensity by up to five orders of magnitude using 1.1 mL min-1 CH4 as reaction gas in a dynamic reaction cell. Polyatomic ion interferences (14N16O1H+, 15N16O+ and 14N17O+ etc.) at m/z 31 were eliminated by detecting P+ as the product oxide ions 31P16O+ using O2 as the cell gas. The poor sensitivity of 31P16O+ was improved to 3-fold by addition of 3 mL-1 methane to the plasma. An extending dynamic range technique based on adjusting the dynamic reaction cell bandpass parameters (RPa) was successfully employed to extend the linearity of 40Ca+ from 1 mg L-1 up to 100 mg L-1. LOD of Ca and P was 0.3 and 4 ng mL-1, respectively. Results of three milk powder standard reference materials were in good agreement with the certified values. The proposed method was applied to determination of 160 milk samples collected from twenty different markets of China and the results of Ca/P ratio ranged from 1.3 to 1.9, which accorded with the official standards (1-2) of FAO/WHO.